Islamic Knowledge and its role in the Development of the Culture and Values of the Islamic Community - المجيد, طالب عبد; فائق, حوراء عدنان (ALBAHITH ALALAMI, 2018)
The human perception of science and knowledge is affected by the personal point of view, thus giving it its religious, mental and emotional dimensions to make that perception an effective tool for realizing the truth comprehensively in the delivery of knowledge to the depths of the human soul. The later is composed of multiple factors, which contributes to the human self-development with dimensions beyond the limits of mental logic and the perception of material and emotional situations. That knowledge in the perception of Islamic virtue, which must characterize each Muslim. Human beings have been striving for knowledge and the understanding of the universe in which they live. For centuries, mankind has acquired knowledge directly and automatically through the use of the main senses of man.The origin of science and knowledge is a gift from God Almighty to humankind through the many channels such as revelation to his messengers. The hearing, sight and heart have been as means of acquiring knowledge. Therefor the Muslim should strive in the search for science and knowledge and their assimilation so that he can employ them in the performance of his duties and the completion of his mandate requirements. Islam knowledge is based on a systematic approach, which is coherent unified focusing on the relations that connect the particles. So the Holy Quran presents ideas and concepts in a comprehensive presentation that explains the purposes of revelation taking the universe, man, and life and their relationship to God Almighty as a source of knowledge and means of conviction and confirmation of faith. Therefore, conducting a study on the importance of Islamic knowledge and its role in society is important, especially in the religious tide found in societies now.